Faktor-faktor Yang berhubungan dengan Perilaku Ibu dalam deteksi Dini Karies Gigi pada Anak Balita di Kecamatan Kuta Utara Kabupaten Badung - Ni Nengah Sumerti (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Low dental caries data eldest among children under five, it does not mean a reduced number of children who suffer from dental caries, but the possibility of lack of maternal attention in detecting the disease cavities in children, as well as the presumption some parents that baby teeth do not need to be treated because it will be replaced by permanent teeth. This study aimed to determine the factors associated with maternal behavior in the early detection of dental caries in children under five in North Kuta Badung District. This study uses quantitative methods to the draft Explanatory Research with cross sectional approach. The sample size was 350 people. Results showed the majority (65.4 %) of early detection practice of dental caries of respondents is less good. The variable that correlates to early detection of dental caries in under five years child is on middle education, good knowledge, good attitude of respondents, the number of information of teeth caries early detection in frequently category is, attitude and good husband’s behavior.